1998
DOI: 10.1016/s0167-4889(98)00126-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB, iNOS mRNA, COX2 mRNA, and COX catalytic activity by phenyl-N-tert-butylnitrone (PBN)

Abstract: Previously, the spin trapping agent phenyl-N-tert-butylnitrone (PBN) has been shown to decrease the level of nitric oxide synthase mRNA in vivo. This inhibition is suggested to be an underlying mechanism for PBN's wide variety of pharmacological actions in animal models. However, the determination of PBN's cellular pharmacological activities has not been carried out, but is necessary for the understanding of the effects in vivo. Since the known pharmacological effects of PBN are primarily anti-inflammatory in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
51
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 36 publications
3
51
0
Order By: Relevance
“…PBN has been shown to be neuroprotective in many neurodegenerative diseases, such as Alzheimer's disease (Floyd et al, 2002;, LPS-mediated septic shock (Sang et al, 1999), hypoxia-ischemia (Lin et al, 2004(Lin et al, , 2006, and stroke (Green et al, 2003). The neuroprotective action of PBN has been attributed to many factors, including formation of a spin adduct with the free radical (Green et al, 2003, Lee andPark, 2005), suppression of ROS production from mitochondria , inhibition of the induction of pro-inflammatory cytokines and iNOS (Kotake et al, 1998;Lin et al, 2006;Sang et al, 1999), inhibition of nuclear factor-kappa B (NF-κB, a transcription factor for a wide variety of pro-inflammatory cytokine genes) (Kotake et al, 1998;Sang et al, 1999), and its anti-apoptosis properties (Lee and Park, 2005;Li et al, 2001). We have shown in our previous study that developing OLs were under oxidative and nitrosative stress following LPS injection and the death of O4 OLs was a result of such a stress (Fan et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…PBN has been shown to be neuroprotective in many neurodegenerative diseases, such as Alzheimer's disease (Floyd et al, 2002;, LPS-mediated septic shock (Sang et al, 1999), hypoxia-ischemia (Lin et al, 2004(Lin et al, , 2006, and stroke (Green et al, 2003). The neuroprotective action of PBN has been attributed to many factors, including formation of a spin adduct with the free radical (Green et al, 2003, Lee andPark, 2005), suppression of ROS production from mitochondria , inhibition of the induction of pro-inflammatory cytokines and iNOS (Kotake et al, 1998;Lin et al, 2006;Sang et al, 1999), inhibition of nuclear factor-kappa B (NF-κB, a transcription factor for a wide variety of pro-inflammatory cytokine genes) (Kotake et al, 1998;Sang et al, 1999), and its anti-apoptosis properties (Lee and Park, 2005;Li et al, 2001). We have shown in our previous study that developing OLs were under oxidative and nitrosative stress following LPS injection and the death of O4 OLs was a result of such a stress (Fan et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Kotake's laboratory has recently demonstrated that PBN prevents the enhanced synthesis of NO in brain induced by a direct brain injection of LPS as an experimental model of bacterial meningitis (Endoh et al,' 1999). In Neuro-inflammatory processes in neurodegenerative diseases 399 cellular systems, Kotake's group has shown that PBN at higher levels inhibits LPS-mediated upregulation of iNOS and COX-2 in a macrophage cell line (Kotake et al, 1998). PBN prevented the LPS-mediated NFrB movement to the nucleus.…”
mentioning
confidence: 99%
“…PBN prevented the LPS-mediated NFrB movement to the nucleus. PBN at higher concentration inhibited catalytically the expressed iNOS enzyme but did not act catalytically on the COX-2 enzyme (Kotake et al, 1998). Our group has examined the efficacy of PBN in a series of experiments involving signal transduction processes in cultured rat astrocytes.…”
mentioning
confidence: 99%
“…For instance, chronic low-level administration of PBN to aged rats reverses their age-enhanced susceptibility to stroke even several days after the last dose . Besides its role as a neuroprotectant, PBN also functions as a potent anti-inflammatory agent by virtue of its inhibitory effects on the activation/mRNA synthesis of inflammatory mediators such as p38␣ mitogen-activated protein kinase, nuclear factor-B, inducible nitric oxide synthase, and cyclooxygenase-2 ( Kotake et al, 1998). The pharmacological basis for the neuroprotective, antiaging and anti-inflammatory effects of PBN has been attributed to its radical-trapping properties and has also prompted medicinal chemistry efforts designed to increase the reactivity of PBN toward free radicals (Fevig et al, 1996;Thomas et al, 1996).…”
mentioning
confidence: 99%